Supportive Leadership Style and Staff Motivation in Private Universities in Uganda: Case of Kampala International University - Chrisostom, Oketch; Ruth Komunda, Tumwijukye (Global Journals, 2021)
This study examined the effect of supportive leadership style on staff motivation in private universities in Uganda taking a case of Kampala International University. The study was guided by two specific objectives: (i) to examine the effect of supportive leadership style on energy to work among staff in Kampala International University, and (ii) to examine the effect of supportive leadership style on sustenance of behavior among staff in Kampala International University. The study hypothesized that (i) “supportive leadership style has no significant effect on energy to work among staff in private universities in Uganda” and (ii) “supportive leadership style has no significant effect on sustenance of behavior among staff in private universities in Uganda”. The study adopted a descriptive correlational design to collect data from a sample of 111 respondents with the aid of self –administered questionnaire.